Psychological perspectives of helplessness and control in the elderly - Fry, Prem S.; ScienceDirect eBooks (Amsterdam ; New York : North-Holland ; New York, N.Y., U.S.A. : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1989)
The past few years have witnessed widespread acceptance of the notion that few elderly individuals are willing to stand by silently in the process of growing, and to relinquish whatever actual controls, autonomy or control beliefs they had in the past. Increasingly, old age is viewed as the dynamics of growth in mastery, control and self-efficacy, on the one hand, and a relative decline in psychological and physical resources on the other. It is the intent of this volume to communicate both aspects of these changes, and to offer a comprehensive review of the cross-fertilization of the field of gerontology and the psychology of reactance, freedom and control. Leading psychologists and social science researchers from the United States, Canada and Europe give their views on the meaning and application of control-related constructs having specific implications for the field of human aging. They address themselves to one or more of the major themes, issues or concerns which currently figure in discussions of control beliefs and control constructs as they apply to aging and old age. Written primarily for scholars, researchers and developmental theorists interested in the complexities and generativity of control constructs and their applications for the psychological well-being of older adults, the data and issues presented will be equally informative to gero-psychologists and mental health professionals concerned with healthy adaptive functioning of the elderly.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Control (Psychology) in old age; Helplessness (Psychology) in old age; Aging -- Psychological aspects; Older people -- Psychology; Aged -- psychology; Choice Behavior; Helplessness, Learned; Internal-External Control; Aged; SELF-HELP -- Aging; PSYCHOLOGY -- Developmental -- Adulthood & Aging; Aging -- Psychological aspects; Control (Psychology) in old age; Helplessness (Psychology) in old age; Older people -- Psychology; Aangeleerde hulpeloosheid; Zelfredzaamheid; Ouderen; Psychologische aspecten; Old persons -- Ageing -- Psychological aspects; Electronic books